Trend and Impact of Concomitant CABG and Multiple-Valve Procedure on In-hospital Outcomes of SAVR Patients - Wu, Jing; Cong, Xiaoqiang; Lou, Zhiyang; Zhang, Mingyou (Frontiers in Cardiovascular Medicine, 2021)
background The trends of concomitant CABG and multiple-valve procedures and their impact on in-hospital outcomes in the context of transcatheter aortic valve replacement are unexplored. Methods This was a retrospective cohort study using the administrative database of the U.S. national inpatient sample from 2012 to 2018 to identify patients who underwent SAVR with or without concomitant CABG and/or multiple-valve procedures. Results During the study period, a total of 75,763 representing 378,815 patients underwent SAVR nationwide were identified, of whom 42,993 (55.1%) experienced isolated SAVR, 27,133 (34.8%) underwent concomitant CABG, 5,637 (7.2%) underwent multiple-valve procedures, and 2,298 (2.9%) underwent both concomitant CABG and multiple valve procedures. The rate of multiple-valve procedures increased from 6.1% in 2012 to 9.2% in 2018 (P<0.001 for trend). In-hospital mortality was 2.1%, 3.9%, 7.3%, and 11.2% for isolated SAVR, SAVR with CABG, SAVR with multiple-valve procedures, and SAVR with CABG and multiple-valve procedures, respectively. After propensity matching, compared to isolated SAVR, the risk ratio for in-hospital mortality associated with concomitant CABG was 1.54 (CI 1.39-1.70). In multiple-valve procedures, it was 2.36 (CI 1.97-2.83), and in concomitant CABG and multiple-valve procedures, it was 2.92 (CI 2.29-3.73). Conclusions: The proportion of patients receiving multiple-valve procedures is increasing. While concomitant CABG moderately increased in-hospital mortality, multiple-valve procedures dramatically increased in-hospital mortality and complications, even after propensity score matching